The rhythm that comes from the syllables - Tatit, Luiz (Estudos Semióticos, 2021)
This paper examines Ferdinand de Saussure’s syllable theory as a model built on the basis of the expression plane to investigate the role of stress in the content plane of language. Based on principles formulated by current developments of Tensive Semiotics, it conceives a decelerated stress, composed of various stages of increase and decrease in tonicity, which somehow express the regular rhythm – though subject to paradoxical accidents – of human meaning. It deals, therefore, with an analytical form of stress, since it can be subdivided and examined in each of these gradual stages, which serve as reference to our incessant appreciations of everyday phenomena.